INTEGRATING ARTIFICIAL INTELLIGENCE INTO FOREIGN LANGUAGE PEDAGOGY - Kasimova Malika (Galaxy International Interdisciplinary Research Journal, 2024)
This paper delves into the role of artificial intelligence, focusing on Chat GPT (Artificial Intelligence Generative Pre-trained Transformer), in foreign language education. It examines the potential applications, advantages, and challenges of AI in language learning, highlighting how it offers tailored, engaging, and effective educational experiences. The paper presents various strategies and tips for utilizing Chat GPT in enhancing the process of learning to write and in transforming ideas, as well as converting informal texts into formal formats. It underscores the benefits of AI as an educational tool in foreign language teaching, promoting critical thinking, collaboration, and advanced communication skills. Moreover, the study stresses the importance of combining human judgment with AI assistance in language learning.